2008
DOI: 10.1055/s-2008-1075602
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Cystic Hygroma in Children with Special Reference to OK-432 Therapy

Abstract: During a five-year period, 18 patients with cystic hygroma were treated as follows: 8 patients were treated surgically, 3 patients were treated by sclerosing therapy with Bleomycin (BLM) and 9 patients including 2 secondary to incomplete surgical therapy were treated by sclerosing therapy with OK-432 (Picibanil; Chugai Pharmaceutical Co. Ltd., Tokyo). OK-432 therapy for cystic hygroma showed excellent results; cure was noted in 8 patients, and marked regression with the expectation of subsequent cure was noted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 1 publication
0
11
0
2
Order By: Relevance
“…OK-432 (picibanil) is obtained from a lyophilized mixture of Group A pyogenes streptococcus and because of immunomodulating effect it increases several cytokines, such as interleukin- (IL-) 1, IL-2, interferon gamma, IL-6, and tumour necrosis factor, thus increasing endothelial permeability, accelerating lymphatic drainage, and fostering retraction of cystic cavity [62, 63]. Yura et al [64] and Ogita et al [65] first reported use of intralesional bleomycin and OK-432 with excellent results. Complete resolution was noted in eight out of nine patients treated with intralesional injection of OK-432 by Ogita et al Sainsbury et al [66] observed 100% overall response rate and 40% complete response rate in patients treated with intralesional bleomycin.…”
Section: Discussionmentioning
confidence: 99%
“…OK-432 (picibanil) is obtained from a lyophilized mixture of Group A pyogenes streptococcus and because of immunomodulating effect it increases several cytokines, such as interleukin- (IL-) 1, IL-2, interferon gamma, IL-6, and tumour necrosis factor, thus increasing endothelial permeability, accelerating lymphatic drainage, and fostering retraction of cystic cavity [62, 63]. Yura et al [64] and Ogita et al [65] first reported use of intralesional bleomycin and OK-432 with excellent results. Complete resolution was noted in eight out of nine patients treated with intralesional injection of OK-432 by Ogita et al Sainsbury et al [66] observed 100% overall response rate and 40% complete response rate in patients treated with intralesional bleomycin.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, lack of control has caused this intraabdominal injection to be avoided (1 case reported [13]). …”
Section: Discussionmentioning
confidence: 99%
“…Originally conceived as an immunotherapeutic agent in the treatment of gastric and lung carcinoma, it was used as an experimental sclerosant in the treatment of an LM in 1987 [39]. The protocol for OK-432 is injection of 0.01 mg/mL dilution of OK-432 in physiological serum for the desired volume [39,40]. The therapeutic response of OK-432 is delayed, typically taking about 6 weeks or more.…”
Section: Lymphatic Malformationsmentioning
confidence: 99%